Analysis of Physicochemical Properties, Volatile Flavor Compounds and Bacterial Communities in Broad Bean Paste from Sichuan and Chongqing - TU Dawei, MA Hongneng, LI Jia, KANG Junhan, LIU Wenjun (Shipin Kexue)
In this study, headspace solid-phase microextraction-gas chromatography-mass spectrometry (HS-SPME-GC-MS) coupled with high-throughput sequencing was used to analyze physicochemical properties, volatile flavor compounds and bacterial community structure of broad bean paste from Sichuan and Chongqing. The results showed that the contents of water, salt, total acids and amino nitrogen of the nine tested samples ranged from 54.33% to 70.46%, 12.49% to 16.90%, 0.44% to 1.46% and 0.17% to 0.41%, respectively. Based on their odor activity values (OAVs ≥ 1), a total of 32 volatile substances including 3-methyl-1-butanol, linalool, phenethyl alcohol, isovaleraldehyde, 2-methylbutyraldehyde, phenylacetaldehyde, ethyl phenylacetate, methyl laurate, ethyl laurate, isovaleric acid, 4-ethylphenol, 4-ethyl-2-methoxyphenol were identified as the characteristic flavor compounds of broad bean paste from the two regions, which contributed to the floral, fruity, malty and soy sauce-like flavor characteristics. In broad bean paste, the dominant bacterial phyla were Firmicutes, Proteobacteria and Cyanobacteria, and the dominant bacterial genera were Bacillus, Pseudomonas, Staphylococcus, Oceanobacillus, Lactobacillus and Enterobacter. Orthogonal partial least squares-discriminant analysis (OPLS-DA) was employed to establish a prediction model with good stability for discriminating the nine samples of broad bean paste. Using the cutoff of variable importance in projection (VIP) score > 1, 29 characteristic volatile compounds were selected. Spearman’s correlation analysis found a correlation between the characteristic flavor substances and the dominant bacterial genera in broad bean paste. This study lays the foundation for further in-depth study on broad bean paste from Sichuan and Chongqing, and provides a reference for optimizing the production of related products.